IMPROVING STUDENTS’ DESCRIPTIVE WRITING TEXT THROUGH PICTURE WORD INDUCTIVE MODEL (PWIM) STRATEGY FOR SEVENTH GRADE OF SMP INABA PALEMBANG - Herizal Herizal; Novi Afriani (Edukasi, 2015)
The objectives of this study were to findout (1) whether or not there is significant difference on students’ descriptive writing through Picture Word Inductive Model (PWIM) Strategy for seventh grade of SMP Inaba Palembang. The investigation of population of this study was the seventh grade students of SMP Inaba Palembang in the academic year 2013/2014, which consist of  98 students coming from three classes. The sample of the study were class 7.1 consisting of 33 students was treated as experimental group and class 7.3 consisting of 31 students was treating as control group, which selected using convenience sampling. The obtained data was analyzed by using regression analysis in SPSS (Statistical Package for Social Science) program. The result showed that there was a significant difference on students’ descriptive writing achievement taught using  Picture Word Inductive Model (PWIM) and Teacher Method (GTM) since tvalue 19.484was higher than ttable (t0.05, 62  = 1.99897), it could be stated that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.